Complex system modeling on establishment of construction standard system. Issue 1 (8th April 2014) - Sun, Zhi; Zhang, Shoujian
Abstract : Purpose: – The complexity of the construction standards affects the relevance between the system internal elements. Therefore, research on the systematic effect can make the construction activities get the optimum benefit. The purpose of this paper is to discuss these issues. Design/methodology/approach: – The research reveals the complex adaptive characteristic of the standard system by using system science theory, analyzes the emergent property mechanism of construction standard system, and provides the mathematical form of the system. Findings: – Finally, according to the complex characteristic of standard system, the structure modeling method of complex system is given. This paper provides a new method and theory bases for the construction standard system establishment. Originality/value: – Dynamic, open and non-linear can be considered as the core characteristics of construction standard system in structure, environment and behavior aspects, and that means the standard system is a typical complex system.